Diversity of rotifer fauna of Kolavoi Lake, Chingleput district, Tamil Nadu - Sonia R; R, Ramanibai (Journal of Research in Biology, 2012)
The biodiversity of the rotifer fauna of Kolavoi Lake, Chingleput was studied through weekly sampling programme advocated from Jan 2010 to Nov 2010. Remarkably rich rotifer community consisting of 23 species was recorded including 3 species reported for the first time from Kolavoi Lake. Brachionus forficula and Keratella vulga were frequently occurred species. Mytilina mucronata, Macrochaetus collinsi and Manfredium eudactylotum are first time reported from this lake.